'I am a bad native': Masculinity and marriage in the biographies of Clements Kadalie. Issue 2 (3rd April 2019) - Dee, Henry
ABSTRACT: Over the course of the 1920s, Clements Kadalie (c.1895–1951) espoused a radical new form of black masculinity that rejected white oversight, disparaged the 'hypocrisies' of colonial 'civilisation', and spurned the established patriarchal practices of other black organisations. As 'bad boy' trade unionists, Kadalie and other leaders of the Industrial and Commercial Workers' Union of Africa were condemned for their bad language and 'debaucheries', but many of these so-called 'faults' were also key to their success as populist leaders of the first mass-member black organisation in southern African history. After Kadalie resigned as general secretary of the ICU, however, he came to see many of these traits as failings and wrote them out of his autobiography, My Life and the ICU, in an attempt to portray a 'worthy story'. Kadalie's early antagonistic relationship with black respectability had fundamentally shifted by the 1940s, as part of his 'revival' as a married, temperate black councillor. Complete with disagreements, divorce, alcoholism, affairs and illegitimate children, this article addresses the awkward place of gender and family in Kadalie's life, and foregrounds aspects of his biography which My Life and the ICU deliberately circumvents. While his first marriage to Molly Davidson ended following numerous affairs, his second wife Eva Moorhead herself had extra-marital relationships and a son by another man. Put in context, Kadalie's autobiographical silences point to wider anxieties over gender, Christianity and citizenship in the retrospective narration of masculine leadership in pre-apartheid South Africa.